Rebalancing the EU-Russia-Ukraine gas relationship - Agata Łoskot-Strachota; Georg Zachmann (Bruegel, 2014)
The October 2014 agreement on gas supplies between Russia, Ukraine and the European Union did not resolve the Ukraine-Russia conflict over gas. The differences between parties in terms of objectives, growing mistrust and legacy issues make it unlikely that a long-term stable arrangement will be achieved without further escalation. Without EU pressure and support, Ukraine is likely to enter a new unfavourable gas arrangement with Russia, which could have repercussions beyond the energy sector. Key highlights: To reduce prices and increase the security of imports, the EU as a bloc should redefine its gas relationship with Russia and Ukraine and overcome the diverging interests of EU member states on second-order issues. Implementation of a joint strategy rests on enforcement of EU competition and gas market rules, a strengthened role for the Energy Community and the establishment of a market-based instrument for supply security. For Ukraine, the EU should serve as an anchor for comprehensive gas sector reform. Contingent on Ukraine's reform efforts, EU financial and technical assistance, the enabling of reverse flows from the EU to Ukraine and pressure on Gazprom, should eventually enable Ukraine to obtain a sustainable gas-supply contract with Russia. This should make a sustainable and mutually beneficial Russia-Ukraine-EU gas relationship possible. However, during the transition, the EU should be prepared for possible frictions.
Keywords: 330